Clinical Aspects of Natural and Added Phosphorus in Foods - Gutiérrez, Orlando M.; Kalantar-Zadeh, Kamyar; Mehrotra, Rajnish (Springer New York : Imprint: Springer, 2017)
This comprehensive reference covers the impact of dietary phosphorus in phosphorus physiology, public health and the pathogenesis of disease. Divided into three parts, the first section is an overview of the history of phosphorus and the regulation of phosphorus homeostasis. The second section focuses on specific matters related to phosphorus in the food supply. Clinical applications of the material presented in the preceding sections are pulled together in the third section - including the importance of both phosphorus excess and phosphorus deficiency for the pathogenesis of a wide variety of disease including kidney, cardiovascular, bone and oncologic diseases. Clinical Aspects of Natural and Added Phosphorus in Foods is an indispensable resource for understanding the growing importance of dietary phosphorus content in health and disease, enhancing patient care and moving forward the field of phosphorus science.- Resumé vydavatel
Keywords: fosfor -- fyziologické aspekty; potraviny; phosphorus -- physiological aspects; foodstuffs; elektronické knihy; sborníky; electronic books; papers of several authors